2021
DOI: 10.3390/tropicalmed6020084
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in Ruminants in Yogyakarta, Indonesia: A Serological Survey with Mixed Methods to Identify Risk Factors

Abstract: Leptospirosis is a zoonotic disease occurring worldwide with reproductive symptoms and production losses in livestock, while humans can suffer fatal renal failure. In Yogyakarta Special Province, Indonesia, there have been several outbreaks with high case fatality, demonstrating the public health importance, but there is limited understanding of the epidemiology. This study used an EcoHealth approach to ensure transdisciplinarity and community participation. Seroprevalence of Leptospira in animals was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The potential for transmission of leptospirosis from cattle to humans, especially stocks farmers, needs particular consideration. Importantly, the study results in Kulonprogo district revealed that most stock farmers still do not have adequate knowledge about Leptospira [23].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The potential for transmission of leptospirosis from cattle to humans, especially stocks farmers, needs particular consideration. Importantly, the study results in Kulonprogo district revealed that most stock farmers still do not have adequate knowledge about Leptospira [23].…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of cattle infected with Leptospira was 3.7%, while that of small ruminants was 3.3%. The most dominant serovars found were Hardjo and Icterohemorrhagie [23]. Kulonprogo district is another district in Yogyakarta Province and has similarities in geography, environment, and the techniques used by farmers in managing livestock, which makes it similar to Bantul and Gunungkidul.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nested PCR also helps in detecting more specific and sensitive DNA sites with additional sets of primers [ 86 , 87 ]. However, current trends for leptospirosis diagnosis are the use of both serological and molecular techniques, such as PCR and ELISA (easier than the gold standard serological MAT), for resource-limited countries [ 88 , 89 ]. Additionally, the LAMP technique [ 90 ] to detect a 16S rRNA gene (rrs), is a cost-effective, rapid and high-yield for detecting the pathogenic leptospires in the urine.…”
Section: Diagnosismentioning
confidence: 99%
“…A number of risk factors for getting leptospirosis were identified in many publications elsewhere, in which factors related to behavioral and agricultural characteristics such as being a farmer, using open water source, health practices are significant in developing countries [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%